Sensorium®: The Splash of Sensory Trademarks. Issue 2 (August 2019) - Elliott, Charlene
Abstract: Sensory trademarks present a compelling case in which to explore the senses as "containers of possibility, " and this article explores the emergence and logic of sensory trademarks from a legal and marketers' perspective. Using sensory trademark cases from the United States, I suggest that the current socio-legal environment opens a conversation about what I would call sensory capitalism—the monetization of the senses rather than the propertization of the senses—that requires intellectual property law to properly function. I argue that the sensory model espoused by the trademarking of the senses is one of the mass sensorium, whereby the "audience" universally recognizes marks as designating a particular source or origin of goods. The mass sensorium offers something quite novel, however, because embedded in it is the (corporate) promise of a lingua franca that valorizes all of the senses and generates a type of mediated affect that is shared. Résumé: Les marques de commerce sensorielles sont des concepts intéressants aux fins d'une exploration des sens en tant que « conteneurs de possibilités ». Le présent article explore l'émergence et la logique des marques de commerce sensorielles du point de vue juridique et dans une perspective de commercialisation. En se fondant sur des cas étatsuniens de marques de commerce sensorielles, l'auteur suggère que l'environnement sociojuridique actuel ouvre une discussion sur ce que l'on pourrait appeler le capitalisme sensoriel—soit la monétisation des sens plutôt que l'appropriation des sens—ce qui nécessite le respect du droit de la propriété intellectuelle. L'auteur soutient que le modèle sensoriel adopté par la commercialisation des sens constitue un des sensorium s de masse, selon lequel le « public » reconnaît universellement que les marques désignent une source ou une origine particulière de produits. Le sensorium de masse offre cependant quelque chose de tout à fait novateur dans la mesure où il se base sur la promesse (entrepreneuriale) de lingua franca valorisant tous les sens et générant un type d'affect médiatisé et socialement partagé.